2021
DOI: 10.3389/fphys.2021.719883
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Ventricular Arrhythmogenicity and Cardiac Sympathetic Hyperinnervation in Early Cirrhotic Cardiomyopathy

Abstract: Cirrhotic cardiomyopathy (CMP) is associated with altered cardiac electrophysiological (EP) properties, which leads to the risk of ventricular arrhythmias (VAs). We aimed to evaluate the EP properties, autonomic, and structural remodeling in a rabbit model with early liver cirrhosis (LC). Twelve rabbits were assigned to the sham and LC groups. The early-stage LC was induced by the ligation of the common bile duct. All rabbits received an EP study, VA inducibility test, myocardial, and liver histology staining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Further, there was a reduction of the transient outward current I to and of the delayed rectifier potassium current I Kr which can be appreciated on the surface electrocardiogram as QTc prolongation 43 . These findings were confirmed in a cirrhotic rabbit model where a significant prolongation of both atrial and ventricular effective refractory periods was noted together with increased sympathetic innervation upon histological assessment 44 . Hence, this confirms increased electrical vulnerability for inducing arrhythmias.…”
Section: Atrial Fibrillation In Cirrhosismentioning
confidence: 61%
See 1 more Smart Citation
“…Further, there was a reduction of the transient outward current I to and of the delayed rectifier potassium current I Kr which can be appreciated on the surface electrocardiogram as QTc prolongation 43 . These findings were confirmed in a cirrhotic rabbit model where a significant prolongation of both atrial and ventricular effective refractory periods was noted together with increased sympathetic innervation upon histological assessment 44 . Hence, this confirms increased electrical vulnerability for inducing arrhythmias.…”
Section: Atrial Fibrillation In Cirrhosismentioning
confidence: 61%
“…43 These findings were confirmed in a cirrhotic rabbit model where a significant prolongation of both atrial and ventricular effective refractory periods was noted together with increased sympathetic innervation upon histological assessment. 44 Hence, this confirms increased electrical vulnerability for inducing arrhythmias.…”
Section: Electrical Remodellingmentioning
confidence: 67%
“…Furthermore, patients undergoing LT can experience an acute release of inflammatory cytokines days after surgery, potentially leading to cardiac dysfunction and arrhythmias due to over-activation of the autonomic nervous system [ 37 39 ]. Nevertheless, our patient’s rapid onset of pulmonary congestion and CA, occurring within 6 hours and 21 hours post-LT, respectively, suggests a limited role of surgery-related stress in the development of her ES and aligns more closely with the characteristics of CCM [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 84%
“…It is defined by an impaired cardiac response to stress, a hyperdynamic circulatory state, both diastolic and systolic dysfunctions, and QT prolongation [ 21 , 22 ]. Additionally, other complications of CCM are pulmonary congestion and arrhythmia [ 23 , 24 ]. After transplantation, our patient’s pulmonary function deteriorated, and she experienced ES.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectation, it was found that during CPB overexpression of Sig-1R in PVN deteriorated heart damage with augmented neuroin ammation and increased sympathetic tone. To con rm this, another heart disease model in which sympathetic nerve changes were involved [19] was used. Our nding highlighted the important role of Sig-1R in PVN in regulating sympathetic out ow and provided a new light on therapeutic strategy for treating heart disease.…”
Section: Discussionmentioning
confidence: 99%